2015
DOI: 10.1038/srep09091
|View full text |Cite
|
Sign up to set email alerts
|

Association between hyperglycemia and retinopathy of prematurity: a systemic review and meta-analysis

Abstract: As the role of hyperglycemia in the development of retinopathy of prematurity (ROP) has not been well established, a meta-analysis of the association between hyperglycemia and ROP was conducted. Studies were identified through literature search in MEDLINE and EMBASE up to June 20, 2014 with keywords related to “hyperglycaemia” and “ROP”. Nine eligible studies involving 1939 neonates with 509 cases of ROP were included. Unadjusted analyses showed that hyperglycemia was significantly associated with ROP (Odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…In premature infants, early hyperglycemia coinciding with phase I of ROP contributes to the later progression of the neovascular phase of ROP (Garg et al , ; Ertl et al , ; Chavez‐Valdez et al , ; Kaempf et al , ; Mohamed et al , ; Ahmadpour‐Kacho et al , ; Mohsen et al , ; Au et al , ). We previously reported that low APN levels positively correlate with retinal neovascularization in premature infants and APN mediates the use of essential long‐chain polyunsaturated fatty acids omega‐3 in the retina to prevent pathological angiogenesis in mice (Fu et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In premature infants, early hyperglycemia coinciding with phase I of ROP contributes to the later progression of the neovascular phase of ROP (Garg et al , ; Ertl et al , ; Chavez‐Valdez et al , ; Kaempf et al , ; Mohamed et al , ; Ahmadpour‐Kacho et al , ; Mohsen et al , ; Au et al , ). We previously reported that low APN levels positively correlate with retinal neovascularization in premature infants and APN mediates the use of essential long‐chain polyunsaturated fatty acids omega‐3 in the retina to prevent pathological angiogenesis in mice (Fu et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In very premature infants, hyperglycemia in the early postnatal weeks strongly correlates with later retinal neurovascular development (Garg et al , ; Ertl et al , ; Chavez‐Valdez et al , ; Kaempf et al , ; Mohamed et al , ; Ahmadpour‐Kacho et al , ; Mohsen et al , ; Au et al , ). It is unknown whether or how hyperglycemia suppresses retinal vessel growth.…”
Section: Introductionmentioning
confidence: 99%
“…43 Therefore, further studies with respect to the other risk factors are needed before drawing the final conclusion of lutein's efficacy in phase I ROP. For example, hyperglycaemia is recently observed as a novel risk factor for the development of ROP, [44][45][46][47][48][49][50][51] and hyperglycaemic induction delayed retinal vascular development in neonatal rats. 52 Examining the effects of lutein in the neonatal rodent model of hyperglycaemia-inhibited retinal angiogenesis will help further explore the role of lutein in phase I ROP.…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental oxygen (which exacerbates vessel loss of phase I), low gestational age (which initiates the process secondary to incomplete retinal vascularization at birth) and low birth weight are major risk factors for retinopathy of prematurity[51]. Increasing evidence also shows that a high perinatal glucose level, indicating dysregulated metabolism, in the first few weeks after birth, independently correlates with the later development of all stages of proliferative retinopathy of prematurity[52]. …”
Section: Apn In Retinal Metabolic Diseasesmentioning
confidence: 99%
“…Hyperglycemia in the early postnatal period is strongly associated with later proliferative retinopathy of prematurity[52, 63], indicating the influence of abnormal glucose metabolism in retinopathy. Studies of the influence of hyperglycemia in phase 1 retinopathy of prematurity have been limited by lack of appropriate animal models.…”
Section: Apn In Retinal Metabolic Diseasesmentioning
confidence: 99%